Pengaruh Kompetensi Profesional Terhadap Kinerja Guru MTs Di Kecamatan Mandau - Warman, Defi (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research was conducted at Madrasah Tsanawiyah Nahdhatul Islam in Mandau District. The purpose of this study was to determine the effect of professional competence on the performance of MTs teachers in Mandau District. To achieve this goal, a study was conducted using a sample of 35 people, using the census method. The data analysis method used simple linear regression. Based on the test results on the professional competence variable (X), it was obtained that t count (4.117) was greater than the t table value (2.035) with a significance level of 0.00 <0.05. So it can be concluded that teacher competence has a significant effect on teacher performance at MTs in Mandau District. The R. Square (R2) value is 0.339 or 33.9%, so the percentage of contribution of the independent variable to the dependent variable is 0.33.9 or 33.9% while the remaining 66.1% is influenced by other variables that are ignored or not examined in this study. The recommendation that can be submitted is that the teacher's professional competence variable must carry out continuous scientific development for a better learning plan in order to improve teacher performance at MTs in Mandau District.